The Antarctic Marginal Ice Zone and Pack Ice Area in CMEMS GREP Ensemble Reanalysis Product - Iovino, Doroteaciro; Selivanova, Julia; Masina, Simona; Cipollone, Andrea (Frontiers in Earth Science, 2022)
Global ocean reanalyses provide consistent and comprehensive records of ocean and sea ice variables and are therefore of pivotal significance for climate studies, particularly in data-sparse regions such as Antarctica. Here, for the first time, we present the temporal and spatial variability of sea ice area in the ensemble of global ocean reanalyses produced by the Copernicus Marine Environment Monitoring Service (CMEMS) for the period 1993-2019. The reanalysis ensemble robustly reproduces observed interannual and seasonal variability, linear trend, as well as record highs and lows. While no consensus has been reached yet on the physical source of Antarctic-wide ice changes, our study also emphasizes the importance of understanding the different responses of ice classes, marginal ice zone (MIZ) and pack ice, to climate changes. Modifications of the distribution of MIZ and pack ice have implications for the level of air/sea exchanges and for the marine ecosystem. Analysis of the spatial and temporal variability of ice classes can provide further insights on long-term trends and help to improve predictions of future changes in Antarctic sea ice. We assess the ability of the reanalysis ensemble to adequately capture variability in space and time of the MIZ and pack ice area, and conclude that it can provide consistent estimates of recent changes in the Antarctic sea ice area. Our results show that the Antarctic sea ice area agrees well with satellite estimates, and the hemispheric and regional sea ice area variability are properly reproduced on seasonal and interannual time scales. Although the ensemble reanalysis product tends to slightly overestimate MIZ in summer, results show that it properly represents the variability of MIZ minima and maxima as well as its interannual variability during the growing and melting seasons. Our results confirm that GREP is able to reproduce the observed substantial regional variability, in regions covered by marginal ice.